The leadership practices of construction site managers and their influence on occupational safety: an observational study of transformational and passive/avoidant leadership. Issue 5 (4th May 2019) - Grill, Martin; Nielsen, Kent; Grytnes, Regine; Pousette, Anders; Törner, Marianne
Abstract: More than 20% of all reported occupational accidents in Europe in 2015 occurred within the construction industry. Leadership is an imperative antecedent to occupational safety. Transformational leadership is considered a central aspect of safety-promoting leadership and passive/avoidant leadership is considered a central aspect of poor safety leadership. This study aimed to comprehensively elucidate concrete, real-life transformational and passive/avoidant leadership behaviours through context-specific descriptions of day-to-day interactions between construction site managers and employees. A mixed method design was applied, combining structured observations of construction site managers, with questionnaire responses from construction employees. With this design, common method bias was eliminated. The results provide context-specific examples of transformational and passive/avoidant leadership behaviour. High proportions of observed transformational leadership was found to predict high construction site safety. High proportions of observed passive/avoidant leadership was found to predict low construction site safety. The proportion of transformational leadership behaviour was higher among site managers in Sweden than in Denmark, indicating that national cultural context may be an antecedent to safety leadership among construction site managers. Applying less passive/avoidant leadership and more transformational leadership appears to be an effective way for construction site managers to improve occupational safety in the industry.